2015
DOI: 10.4236/oalib.1101407
|View full text |Cite
|
Sign up to set email alerts
|

Syndemic Theory and Male Same Sex Intimate Partner Violence: An Urban/Non-Urban Comparison

Abstract: Background: The majority of research with gay men has been conducted in urban populations, with minimal work on partner violence in non-urban (suburban and rural) settings. Syndemic theory, the concept that negative health outcomes are increased with the addition of each new deleterious health variable, has been used to understand partner violence. The aim of the study was to determine differences in prevalence and associated factors of male same-sex intimate partner violence (MSSIPV) among gay men residing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
0
6
0
3
Order By: Relevance
“…A notable finding of the scoping review was the number of extracted studies that explored how gay and bisexual men experience distinctive stressors due to their sexual orientation. Such studies explored the distinctive social and cultural factors that impact men’s experiences of violence (Badenes-Ribera et al, 2017; Finneran et al, 2012; Meyer, 1995; Pimentel, 2015; Rollè et al, 2018). Those that examined the intersectionality between IPV and minority status often utilized the minority stress theory put forth by Meyer (1995).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A notable finding of the scoping review was the number of extracted studies that explored how gay and bisexual men experience distinctive stressors due to their sexual orientation. Such studies explored the distinctive social and cultural factors that impact men’s experiences of violence (Badenes-Ribera et al, 2017; Finneran et al, 2012; Meyer, 1995; Pimentel, 2015; Rollè et al, 2018). Those that examined the intersectionality between IPV and minority status often utilized the minority stress theory put forth by Meyer (1995).…”
Section: Resultsmentioning
confidence: 99%
“…Online surveys with 439 bisexual participants revealed that bisexual men were more likely to have higher levels of biphobia about their sexual identity (Turell et al, 2018). Focus groups revealed that bisexual women associated bisexual erasure to feelings of exclusion from LGBTQ health services (Flanders et al, 2017), a problematic finding, as cross-sectional surveys have highlighted that many sexual minority individuals experiencing IPV may not have access to specialized IPV services and may overly depend on LGBTQ-orientated services (Pimentel, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations